Ecocene Politics - Tănăsescu, Mihnea (Open Book Publishers, 2022)
Anchored in the diverse ecological practices of communities in southern Italy and Aotearoa/New Zealand, this book devises a unique and considered theoretical response to the shortcomings of global politics in the Ecocene-a new temporal epoch characterised by the increasingly frequent intrusion of ecological processes into political life. Dismantling the use of the term 'Anthropocene' as a descriptor for our current ecological and political paradigm, this bold and resolutely original contribution proposes a restorative ethics of mutualism. An emancipatory theory intended to re-invigorate human agency in the face of contemporary ecological challenges, it posits an effective means to combat the environmental destruction engendered by modernity. Using ecology alongside European moral and Māori philosophies to re-conceptualise the ecological remit of politics, this book's granular approach questions the role played by contemporary political ontologies in the separation of humans and environments, offering an in-depth view of their renewed interrelation under mutualism. Ecocene Politics will be essential to researchers and students in the fields of politics, philosophy, sociology, anthropology, and geography. It will be of further interest to those working in the fields of political ecology, environmental humanities, and Anthropocene studies, as well as to general readers seeking a theoretical approach to the political issues posed by current ecological crises.